The response of biological communities to natural and anthropogenic habitat fragmentation in South Outeniqua Sandstone Fynbos, South Africa - Sandberg, Rory Nimmo (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.